Finishing Barn Cost Return Projection - Dhuyvetter, Kevin C.; Tokach, Mike D. (My University, 2004)
This publication provides estimated cost and returns for a finishing barn.
MF2152_2004_10
Keywords: MF2152; Livestock; Economics; MF